Hubungan Kesabaran Dengan Perilaku Konsumtif Terhadap Produk Makeup Pada Mahasiswi Psikologi Universitas Islam Riau - Leviabriani F, Desry; Hidayat, Ahmad; Ariqoh S, Seishin (UIR Press, 2023)
Consumptive behavior in purchasing makeup products has become a lifestyle among female students. Makeup products are attached to women because basically women are creatures that are synonymous with beauty. This is what causes women to like to buy cosmetic products with a plan or without a plan. One component of patience is self-control, namely being able to restrain desires and emotions, think long-term, forgive and have tolerance. This research was conducted in order to find out whether or not there is a relationship between patience and consumptive behavior towards makeup products in Riau Islamic University female students. The study population was 743 female students, with a total sample of 260 active semester psychology students at the Islamic University of Riau, which were determined using the accidental sampling technique.The data collection method uses a modified patience scale from Kencana and a modified consumptive behavior scale by Nafli. In this data were analyzed using the Spearman Rho method with a correlation coefficient of -0.099 and a significance value of 0.113 (p > 0.05). This clarifies the rejected hypothesis so that there is no relationship between patience and consumptive behavior towards makeup products of psychology students at Islamic University of Riau.